2023
DOI: 10.3390/w15020240
|View full text |Cite
|
Sign up to set email alerts
|

Review of In-Situ and Remote Sensing-Based Indices and Their Applicability for Integrated Drought Monitoring in South Africa

Abstract: The devastating socioeconomic impacts of recent droughts have intensified the need for improved drought monitoring in South Africa (SA). This study has shown that not all indices can be universally applicable at all regions worldwide, and there is no single index that can represent all aspects of droughts. The aim of this study was to review the performance and applicability of the Palmer drought severity index (PDSI), surface water supply index (SWSI), vegetation condition index (VCI), standardised precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 70 publications
(204 reference statements)
0
18
0
Order By: Relevance
“…There are two types of connections that drought parameters can show: linear and nonlinear [24,25]. Drought frequency and intensity have been effectively proved by the probability density functions (PDFs) of drought indices [26,27,28].…”
Section: Objectivesmentioning
confidence: 99%
“…There are two types of connections that drought parameters can show: linear and nonlinear [24,25]. Drought frequency and intensity have been effectively proved by the probability density functions (PDFs) of drought indices [26,27,28].…”
Section: Objectivesmentioning
confidence: 99%
“…Field phenotyping using modern high-throughput infrastructures and precision agriculture techniques is better developed in South Africa compared to other countries on the continent ( Nyaga et al., 2021 ; Mukhawana et al., 2023 ). Some research groups are making efforts in championing field phenotyping and precision agriculture through workshops and implementation of UAV remote sensing applications and other approaches for agricultural monitoring (stress detection, nutrient and irrigation management) ( https://www.fabinet.up.ac.za/index.php/research-groups/remote-sensing ).…”
Section: Overview Of the Status Of Field Phenotyping In Africamentioning
confidence: 99%
“…They further confirmed that this multivariate drought index captures the duration of drought reasonably well, affirming the Frank‐copula as the best‐fitted copula function for the basin. Other studies (Cheng et al., 2023; Derradji et al., 2023; Jiao et al., 2021; Mukhawana et al., 2023; Nugraha et al., 2023) categorized drought based on remote sensing approaches. Despite the importance of multivariate approaches to drought assessment (Hao & AghaKouchak, 2013), there is still a gap in the use of MSDI‐based drought indicators to provide information on drought propagation and projection.…”
Section: Introductionmentioning
confidence: 99%